I am a bit puzzled. Trying to solve this system of equations:

\begin{align*} -x + 2y + z=0\\ x+2y+3z=0\\ \end{align*}

The solution should be \begin{align*} x=-z\\ y=-z\\ \end{align*}

I just don't get the same solution. Please advice.

  • $\begingroup$ what solution did you obtain? to correct your mistake, I believe we need to know your working. $\endgroup$ – Siong Thye Goh Sep 19 '17 at 17:19
  • $\begingroup$ first, add the equations and see what you get. Then subtract the equations. $\endgroup$ – Vasya Sep 19 '17 at 17:19
  • $\begingroup$ According to my lecture notes I have now: \begin{align*} -x + 2y + z=0\\ y+z=0\\ \end{align*} But how to get to this point? I don't understand how it leads to this... $\endgroup$ – MiMaKo Sep 19 '17 at 17:26

adding both equations we get $$y=-z$$ plugging this in the first equation we get $$-x-2z+z=0$$ tgherefore $$x=-z$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.